(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
The application of a correct and detailed traceability provides knowledge of unsafe or harmful food and of food unfit for human consumption, in relation to the processes of re- call to be applied in case of withdrawal of the product, at any stage of the food chain. Penalties are proportionate to the gravity of the violations. The authors analyze the penalties imposed at national level on operators of food industry, in all stages of production. In particular they analyze violations of EC Regulation n. 178/2002 on traceability .